2020
DOI: 10.33271/mining14.03.112
|View full text |Cite
|
Sign up to set email alerts
|

Improving the technology of uranium mining under the conditions of high groundwater pressure

Abstract: Substantiation of technological solutions for uranium mining by the method of In-Situ Leach Mining (ISL) under the conditions of the high groundwater pressure. Methods. Analysis of mining-and-geological conditions of the deposit, conducting experimental-industrial works at the experimental unit, and processing data from research results. To increase the efficiency and reduce the expenditures for insitu leach mining of uranium, taking into account the hydrogeological peculiarities of the deposit, experimental w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This method is the most cost-intensive due to the use of a large number of equipment, chemical reagents, maintenance personnel and a long duration of the works. However, these methods are ineffective in difficult mining-and-geological conditions, as multicomponent sedimentations are accumulated in the near-filter zone and form cemented impermeable areas that are not amenable to conventional stimulation methods [17], [18].…”
Section: Figure 3 Location Map Of Regions With Explored Uranium Deposits In Kazakhstanmentioning
confidence: 99%
“…This method is the most cost-intensive due to the use of a large number of equipment, chemical reagents, maintenance personnel and a long duration of the works. However, these methods are ineffective in difficult mining-and-geological conditions, as multicomponent sedimentations are accumulated in the near-filter zone and form cemented impermeable areas that are not amenable to conventional stimulation methods [17], [18].…”
Section: Figure 3 Location Map Of Regions With Explored Uranium Deposits In Kazakhstanmentioning
confidence: 99%
“…Recently, the scope of ISL technology embraces geologically unfavorable reservoirs, with low uranium content, low permeability, high clay content and without ferric iron in rock mass and in reservoir water [5][6][7]. As a consequence, the uranium recovery efficiency in production blocks is round 50% at the sulfuric acid content of 10-15 g/l in leach solutions for easy compounds and round 80% at the solution acidity of 20-25 g/l for difficult uranium.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of different techniques intensifying leaching has shown that they accelerate the process and increase several times useful mineral extraction [28], [29]. Nevertheless, they are not versatile and depend upon conditions of specific deposits.…”
Section: Introductionmentioning
confidence: 99%